2022
DOI: 10.3390/ijms232415644
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity and Chromosomal Rearrangements in Neisseria gonorrhoeae and Neisseria meningitidis

Abstract: Chromosomal rearrangements in N. gonorrhoeae and N. meningitidis were studied with the determination of mobile elements and their role in rearrangements. The results of whole-genome sequencing and de novo genome assembly for 50 N. gonorrhoeae isolates collected in Russia were compared with 96 genomes of N. gonorrhoeae and 138 genomes of N. meningitidis from the databases. Rearrangement events with the determination of the coordinates of syntenic blocks were analyzed using the SibeliaZ software v.1.2.5, the min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…DNA repeat sequences could be targeted by recombination processes leading to amplifications, deletions, and rearrangements of genetic material [47,52,53]. In this study, we identified 156 rearrangement events caused by TRIP1 repeat sequences in 6725 E. coli genomes (Figure 5).…”
Section: Discussionmentioning
confidence: 92%
“…DNA repeat sequences could be targeted by recombination processes leading to amplifications, deletions, and rearrangements of genetic material [47,52,53]. In this study, we identified 156 rearrangement events caused by TRIP1 repeat sequences in 6725 E. coli genomes (Figure 5).…”
Section: Discussionmentioning
confidence: 92%
“…A total of 29 collections were taken, including genomes of 14,763 isolates from 68 countries ( Supplementary Figure S1, Supplementary Table S1 ). The final sample also comprised 61 genomes of the Russian isolates described earlier [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first MITEs described in Bacteria were the so called 'Correia elements' of N. gonorrhoeae and N. meningitidis (36,37), and their destabilizing role of the genome was demonstrated after the analysis of the transcriptional regulation of several Neisseria genes (38). Negative effects related to transposition events have been described so far, such as gene inactivation, alteration of gene function, genomic rearrangements, modification of the genome structure (formation of secondary structures), or genomic instability leading to accumulation of mutations (30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)). Importantly, MITEs have been also related with the genes dispersion of antimicrobial resistance in Acinetobacter and Enterobacter cloacae (49)(50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%